Hybridising as an Artists' Problem. Some Theses (ENTHYMEMA, 2010)
The article proposes a theoretical reflection on the notion of «hybridization» and a critique of its ideological use. The concept of «hybrid» is treated as a starting point rather than as a result. The possibility of defining a classification is questioned on the basis of some fundamental reflections by Nietzsche, who, in Beyond Good and Evil, distinguishes between fertile hybridizations, where the different elements are strenghtened by their mixing and the various forces are combined, and bad or sterile hybridizations, where the various forces, rather than reciprocally stimulate themselves, hinder and paralyze each other. The author believes that this distinction can play a crucial role both in the arts and in politics.